Pengembangan Sistem Informasi Manajemen Ternak Burung Lovebird berbasis Android - Akhsana Zufar Masyhuda; Nurudin Santoso; Edy Santoso (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Lovebird is one kind of parrot that has an attractive feather color and distinctive sound. That's make birds form Africa have a fairly high selling value and some people are interested doing lovebird bird cultivation. The bird breeders have not yet realized the importance of recording on cultivated bird. Another problem that often arises in the field of aviculture is that farmers still record everything related to finance still in a manual way. The solution for those problems is by providing information system that can help farmers to collect data and everything related to activities of cultivation activities both in terms of data collection of cultivated birds and from the financial side used during the bird cultivation process. In this research, system development was carried out using the Rapid Application Development method and using an object oriented approach. In this research, there were 3 factors tested validation, unit, and usability. Validation and unit testing produces 100% valid. Whereas to test usability get overall points 0.94 which indicates that the system is usable for end-user.